Operation Varsity Blues: Disguising the legal capital exchanges and white property interests in athletic admissions (Higher Education Politics and Economics, 2019)
“Operation Varsity Blues” (OVB) indicted coaches and administrators from eight universities for accepting bribes in exchange for admitting fraudulent athletes. As part of the conspiracy parents paid university officials to admit students with little-to-no sport experience as college athletes. Court filings in the case contrasted OVB to the legal process of athletic recruitment and admission in which universities set different criteria to admit those with athletic talent (Smith, 2019a). This conceptual article cautions against such a contrast. Using Harris’ (1993) whiteness as property, Bourdieu’s (2011) capital exchange theory, and findings from my research into athletic recruitment and admission, I examine how OVB closely resembles current athletic admissions practices that provide a legal pathway to college that privileges white, elite communities.